Music and Psyche: Towards a Theory of Individual and Relational Psycho-sonorous Profiling - Pellizzari, Patricia; Basutto, Alfonsina (Voices: A World Forum for Music Therapy, 2006)
The foundations of this project were based mainly on questions about music therapeutic clinical practice, a practice whose efficacy has been demonstrated and it's expanding every day through its innovative practice-based procedures. The general goal of our study was to formulate a specific theoretical approach contributing to diagnostic evaluation in the area of mental health. The design was exploratory and descriptive. The analysis of the data was carried out with a mixed methods procedure; some variables were treated qualitatively and some quantitative procedures were carried out as well.Through this combined procedure two analysis units were evaluated: Sonorous Production Analysis Unit, given by the variables of dynamic organization from Individual Improvisation and the variables of connection in the relational improvisation, and Subject Unit given by psychological variables (organization of thoughts, symbolization, affectivity, receptivity, etc...) of the verbal interview and the variable Subjective Appreciation from the interviewed about the relationship PS and psychological features given by a written questionnaire.After carrying out the empirical phase, defining all the variables and designing the charts of reported data, the information was processed with a SPSS Statistical package. Through quantitative and qualitative procedures we have been able to determine five individual sonorous profiles (random, germ, stable, complex and creative), five relational sonorous profiles (isolated, fused, dependent, differentiated and integrated) and significant relationships for its correlational tendencies between these profiles and the psychological variables. In this paper the results of the first stage will be developed.